A PERCEPÇÃO DO PACIENTE SOBRE PROCEDIMENTOS CIRÚRGICOS: INTERFACES ENTRE LINGUAGEM E SAÚDE - JABBOUR, Vitor,; MACIEL, Ruberval Franco,; FERNANDES, André Luis Marcondes,; SILVA, Izabella Cristina,; THEODOROVITZ, Armando Tomaz,; PALOMARES, Danielly Larissa Pereira, (ANAIS DO ENIC, 2023)
-